1983
DOI: 10.1590/s0373-55241983000200008
|View full text |Cite
|
Sign up to set email alerts
|

Primary production of the benthic microflora living on intertidal flats in the Santos estuarine system (24ºS, 46ºW), São Paulo, Brazil

Abstract: Estimates of primary produetion of benthic microflora were carried out in the Santos tropical estuary, on the southern coast of Brazil (24ºS, 46ºW). The samples were obtained seasonally over a one-year period. Six stations with different environ mental conditions were chosen. The samples, which consisted of the upper 2 mm of the sediment, were collected in the intertidal zone, according to Grøntved's (1960) methodology. The mean annual value of primary production was 45 mgC/m²/h, ranging from 1. 0 to 301.0 mgC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, there are only a few studies involving estuarine microphytobenthos (Sousa, 1983;Sousa & David, 1995) or meiofauna (Dalto & Albuquerque, 2000;Gomes et al, 2002;Somerfield et al, 2003;Rosa & Bemvenuti, 2005). For the meiofauna, all these studies have identified the organisms only to higher taxonomic level (phyla or class).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are only a few studies involving estuarine microphytobenthos (Sousa, 1983;Sousa & David, 1995) or meiofauna (Dalto & Albuquerque, 2000;Gomes et al, 2002;Somerfield et al, 2003;Rosa & Bemvenuti, 2005). For the meiofauna, all these studies have identified the organisms only to higher taxonomic level (phyla or class).…”
Section: Introductionmentioning
confidence: 99%